Dynamic analysis of adsorption and diffusion of volatile organic compounds in zeolite pellets - Akosman, Cevdet; Kalender, Mehmet (Parlar Scientific Publications (P S P), 2007)
The vapour-phase adsorption and diffusion of water-miscible volatile organic compounds (methanol) and water-immiscible ones (benzene) in zeolite 4A-pellets were investigated by single pellet moment technique. The experiments were carried out in a one-sided single pellet adsorption cell using varying relative humidities (0-40%) at 30 degrees C. In both dry and wet systems, the adsorption of volatile organic tracers used was found to be adsorbed reversibly onto the zeolite 4A-pellet. The overall adsorption equilibrium constants of both tracers decreased with the increase of relative humidity, but the adsorption equilibrium constant of methanol was more than that of benzene at all relative humidities. The effective diffusivity of benzene in zeolite pellet did not show a considerable change with relative humidity. On the other hand, there was an appreciable change in effective diffusivity for methanol with moisture.
Keywords: adsorption constants; effective diffusivity; zeolite 4A; volatile organic components; water vapour